DETERMINANTS OF TRANSFER PRICING - Lutfi Annisa; Prima Apriwenni (Sean Institute, 2023)
The results of research that have been conducted so far related to transfer pricing show inconsistencies in independent variables that affect transfer pricing. In addition, in 2019-2021, several companies were still found to carry out[1] transfer pricing practices that needed to be by the rules, causing state losses. This study examines the effect of the effective tax rate, bonus mechanism and debt covenant on transfer pricing. The research was conducted on manufacturing companies on the Indonesia Stock Exchange in 2019-2021. Signal theory, agency and positive accounting were used as the theoretical basis for this study. The sampling method used purposive sampling and obtained sample data of 33 samples. The analysis technique used is the multiple regression analysis technique. This study concluded that there is insufficient evidence that effective tax rates, bonus mechanisms and debt covenants positively affect transfer pricing.